Conversion of propanal to pentan-3-one using lanthanide oxides - Claridge, J; Green, M; Tsang, S; York, A (1993)
The heterogeneous reaction between propanal vapour and rare-earth-metal oxides gives as major products pentan-3-one and carbon dioxide. Residence time investigations indicate that pentan-3-one and carbon dioxide are primary products. Deactivation and high-resolution electron microscopy studies support the hypothesis that surface [O] participates in the reaction, and high oxygen mobilites in the oxide may allow defects to spread within the oxide. The carbon dioxide produced in the reaction poisons the lanthanum oxide leading to the faster deactivation and temperature-programmed desorption indicates the presence of a surface intermediate which decomposes to pentan-3-one and carbon dioxide. A mechanism is proposed in which the formation of pentan-3-one proceeds via surface-bound carboxylate species. Preliminary studies show that catalytic production of pentan-3-one can potentially be sustained by co-feeding water with propanal to the rare-earth-metal oxides.